Genome-wide gene-environment interaction analysis of pesticide exposure and risk of Parkinson's disease. (November 2016) - Biernacka, Joanna M.; Chung, Sun Ju; Armasu, Sebastian M.; Anderson, Kari S.; Lill, Christina M.; Bertram, Lars; Ahlskog, J.E.; Brighina, Laura; Frigerio, Roberta; Maraganore, Demetrius M.
Abstract: Introduction: Genetic factors and environmental exposures, including pesticides, contribute to the risk of Parkinson's disease (PD). There have been few studies of gene and pesticide exposure interactions in PD, and all of the prior studies used a candidate gene approach. Methods: We performed the first genome-wide gene-environment interaction analysis of pesticide exposure and risk of Parkinson's disease. Analyses were performed using data on >700, 000 single nucleotide polymorphisms (SNPs) in 364 discordant sibling pairs. In addition to testing for SNP-pesticide interaction effects, we also performed exploratory analyses of gene-pesticide interactions at the gene level. Results: None of the gene-environment interaction results were significant after genome-wide correction for multiple testing (α = 1.5E-07 for SNP-level tests; α = 2.1E-06 for gene-level tests). Top results in the SNP-level tests provided suggestive evidence ( P  < 5.0E-06) that the effect of pesticide exposure on PD risk may be modified by SNPs in the ERCC6L2 gene ( P  = 2.4E-06), which was also supported by suggestive evidence in the gene-level analysis ( P  = 4.7E-05). None of the candidate genes assessed in prior studies of gene-pesticide interactions reached statistical support in this genome-wide screen. Conclusion: Although no significant interactions were identified, several of the genes with suggestive evidence of gene-environment interaction effects have biological plausibility for PD risk. Further investigation of the role of those genes in PD risk, particularly in the context of pesticide exposure, in large and carefully recruited samples is warranted. Highlights: Environmental and genetic risk factors contribute to the development of PD. There have been few studies of gene and pesticide exposure (PE) interactions in PD. We present a genome-wide gene-environment interaction analysis of PE and risk of PD. Several top results may implicate genes with biological plausibility for PD risk. Further investigation of the role of these genes in PD risk is warranted.